2016
DOI: 10.1016/j.cell.2016.05.032
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of an Active RAG Transposon Illuminates the Origins of V(D)J Recombination

Abstract: SUMMARY Co-option of RAG1 and RAG2 for antigen receptor gene assembly by V(D)J recombination was a crucial event in the evolution of jawed vertebrate adaptive immunity. RAG1/2 are proposed to have arisen from a transposable element, but definitive evidence for this is lacking. Here we report the discovery of ProtoRAG, a DNA transposon family from lancelets, the most basal extant chordates. A typical ProtoRAG is flanked by 5 bp target site duplications and a pair of terminal inverted repeats (TIRs) resembling V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
195
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(211 citation statements)
references
References 46 publications
(66 reference statements)
6
195
0
1
Order By: Relevance
“…4G, 6–7), and the proper communication between RNH domains depends on the NBD domains binding to nonamers. Acquisition of the NBD domain by RAG1 differentiates the chordates that carry out V(D)J recombination from those that do not (Huang et al, 2016). It may be surprising that the truncated RAG1/2 without NBD binds RSS DNAs as well as core RAG1/2 but fails to cleave them (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…4G, 6–7), and the proper communication between RNH domains depends on the NBD domains binding to nonamers. Acquisition of the NBD domain by RAG1 differentiates the chordates that carry out V(D)J recombination from those that do not (Huang et al, 2016). It may be surprising that the truncated RAG1/2 without NBD binds RSS DNAs as well as core RAG1/2 but fails to cleave them (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Questions remain as to whether RAG2 was part of the original transposon or whether it was an existing gene in the genome recruited to assist RAG1 in gene rearrangement 100,101 . Note that the RAGs are not used for VLR gene rearrangement in agnathans (see below), yet as mentioned, RAG1-like and RAG2-like genes have been found in the genomes of lower deuterostomes whose ancestors predated the vertebrates, such as sea urchins and amphioxi, where their functions, if any, are unknown 100,102 .…”
Section: Evolution Of Antigen Receptorsmentioning
confidence: 99%
“…In addition to RAG1 , RAG2 also was shown to have TE origins and several lines of evidence suggested that both RAG1 and RAG2 were domesticated from the same ancestral Transib element [26]. This evolutionary scenario has been solidified by a recent study that functionally characterized an active Transib element from the lancelet, a member of the cephalochordates, which lack V(D)J recombination [27]. This transposon, coined ProtoRAG , encodes both RAG1 - and RAG2 -like genes arranged just like their domesticated vertebrate homologs and flanked by TIRs that resemble the RSS and is able to undergo TIR-dependent transposition through a mechanism strikingly similar to RAG1/2-mediated DNA rearrangement [27].…”
Section: Conflicts Between Hosts and Pathogensmentioning
confidence: 99%